2018
DOI: 10.1002/joc.5822
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different large‐scale predictor‐based statistical downscaling models in simulating zone‐wise monsoon precipitation over India

Abstract: Selection of suitable predictors for downscaling local-scale precipitation from the wide range of large-scale predictors available in National Center for Atmospheric Research/National Centers for Environmental Prediction (NCAR/NCEP) reanalysis is a challenging task because of the existence of the complex interactions between local-scale predictands and large-scale predictor fields. An attempt was made to assess how well different large-scale predictors were able to reproduce local-scale monsoon precipitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…They reported that the reasons for differing results related to climate change are related to the inconsistent use of both climate and hydrologic models, emission scenarios, and GCM output downscaling techniques. Akhter et al (2018) also reported that differences in rainfall projections may occur due to the variations of atmospheric domain sizes which determine the hydroclimatology of a watershed by affecting the selection and number of sensible predictors.…”
Section: Climate Change In the Andasa Watershedmentioning
confidence: 99%
“…They reported that the reasons for differing results related to climate change are related to the inconsistent use of both climate and hydrologic models, emission scenarios, and GCM output downscaling techniques. Akhter et al (2018) also reported that differences in rainfall projections may occur due to the variations of atmospheric domain sizes which determine the hydroclimatology of a watershed by affecting the selection and number of sensible predictors.…”
Section: Climate Change In the Andasa Watershedmentioning
confidence: 99%
“…Spatial fitting, selection of monthly fields from the WRF model, and spatial selection of the best monthly products of global grid precipitation are analyzed for each regional domain (Figure 1A): The results of these processes are displayed for eight hydrological basins (Figure 1B). Our strategy uses a range of statistics following Cardoso et al (2013), Ji et al (2015), and Akhter et al (2019): standardized standard deviation (σ e , Eq. 6), standardized mean square error (nrmse, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The categories of predictors are (a) circulation variables (Geo‐potential height, mean sea level pressure, u and v wind components), (b) moisture variables (specific and relative humidity, precipitable water) and (c) thermal variable (temperature) at different pressure levels that is, 500, 850 and 1,000 hPa. All the considered predictors for the present study, have been previously used for downscaling over Indian domain (Pervez and Henebry, ; Akhter et al, ). Although large‐scale atmospheric circulation may explain local precipitation behaviour, other variables such as humidity and temperature in various atmospheric levels that are not directly related to pressure field could also play a significant role in controlling precipitation on smaller scales (Abaurrea and Asín, ).…”
Section: Methodsmentioning
confidence: 99%
“…K E Y W O R D S CMIP5 models, perfect prognosis, performance metrics, principal component regression, quantile mapping, statistical downscaling 1 | INTRODUCTIONThe recent two generations of the global climate models (GCMs) from the fourth and fifth assessment reports of the IPCC, providing a range of horizontal resolutions 103 to 455 km (average of 254 km) in case of coupled model inter comparison project phase 3 (CMIP3) and 68 to 342 km (average of 193 km) in case of coupled model inter comparison project, phase 5 (CMIP5), are still considered as coarse grid models because they are usually unable to incorporate local/regional scale features like topography, clouds, land-use etc. adequately (Sachindra et al, 2014;Akhter et al, 2018). The scale mismatch between the GCM outputs and the hydroclimatic information needed at the catchment level is a major obstacle in climate impact assessment studies of hydrology and water resources (Willems and Vrac, 2011).…”
mentioning
confidence: 99%